LARVICIDAL EFFICACY OF SCINDAPUS OFFICINALIS AGAINST AEDES AEGYPTI, A DENGUE FEVER VECTOR - Sreedev, P.; Ali, K. Misvar; Aneesh, E. M. (Journal of Dharma, 2014)
The larvicidal efficacy of petroleum ether extract of Scindapus officinalis against the fourth instar larvae of Aedes aegypti was studied. Insecticidal susceptibility tests were done according to WHO standard procedure and the mortality was observed after 24 hours of exposure. The extract showed potential larvicidal efficacy with LC50 value of 3.18 mg/L. This is a pioneer attempt to explore the larvicidal activity of this plant. The petroleum ether extract of its fruit showed potential larvicidal efficacy even at very low concentrations. Further, the biochemical mechanism and mode of action are under investigation and warrants extensive study. The development of an effective eco-friendly mosquitocide of plant origin may reduce the risk of wide use of synthetic insecticides as mosquito control agents.